Project management process of Engineering and Site Services (ESS) at British American Tobacco Bangladesh - Ferdous, Rounak (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.